Effect of fly ash on rheological properties of graphene oxide cement paste. (1st May 2017) - Wang, Qin; Cui, Xinyou; Wang, Jian; Li, Shiyu; Lv, Chunxiang; Dong, Yichen
Graphical abstract: Highlights: Fly ash (FA) increases fluidity and workability of graphene oxide (GO) cement paste. Fly ash improves the rheological properties of cement paste with graphene oxide. Shear rates, shear stress, yield stress and plastic viscosity of FA-GO-cement are delineated. A mechanism that can lessen viscosity in FA-GO cement paste was developed. Abstract: While graphene oxide (GO) is found to have a potential to enhance the strength and toughness of cement based composites, it may reduce the cement paste fluidity and thus the workability of concrete. In this paper, a simple and economical additive, fly ash, is investigated to improve the rheological properties of cement paste when GO is present. Based on the quantitative analysis of the rheological parameters, it's shown that fly ash can offset the reduction of fluidity by GO. The effect of fly ash was studied with two dosages of GO, 0.01 wt% and 0.03 wt%. The yield stress and plastic viscosity of cement paste decreased with the increase of fly ash. At 0.01 wt% of GO and 20 wt% of fly ash, the yield stress of the paste decreased 85.81% and the plastic viscosity decreased 29.53% in comparison to the control sample (no fly ash or GO). At 0.03 wt% of GO and 20 wt% of fly ash, the yield stress of the paste is 50.33% lower and the plastic viscosity decreased slightly by 5.58%.The hysteresis area of the composite paste also decreased with the increase of fly ash. Meanwhile, the results indicated a good correlation between the fluidity and the plastic viscosity. The "ball" effect, grain size gradation and less water demand of fly ash can play an important role in improving the fluidity of the GO-cement systems. Moreover, GO can offset the delay in early-stage strength gain of fly ash-cement systems. When the dosage of fly ash is less than 15 wt%, the compressive and flexural strength of fly ash-GO-cement composites are all higher than the control sample at 3, 7, and 28 d. This indicates that the addition of fly ash is an economical and effective method to obtain desirable properties of GO-cement paste. The benefits of mixing fly ash and GO can help counteract the fluidity problems of the GO-cement paste on the workability of concrete.